Sektor Industrialisasi dan Pengelompokan pada Perusahaan Negara - Muhammad Naufal Mahbub; Meiske Marlisye Makuku; Muhammad Yasin (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
Industrialization is a key factor in the economic development of a country, including Indonesia. Since the New Order era, industrialization has become an integral part of national development strategies, marked by the growth of the industrial sector and the active involvement of state-owned enterprises (SOEs). This study aims to provide a comprehensive understanding of the concept of industrialization, its role in the economy, the development of the industrial sector in Indonesia, its impacts, and concrete examples of state-owned enterprises operating in the industrial sector. The method used is a literature review with a qualitative approach, focusing on synthesizing findings from various sources to gain deeper insight. The discussion results show that industrialization greatly contributes to economic growth and job creation, but it also brings negative impacts such as environmental pollution, consumerism, cultural value shifts, and uncontrolled urbanization. One example of a state-owned enterprise playing a major role in the industrial sector is PT Pertamina (Persero), which contributes to national energy security and the development of a sustainable energy industry. By understanding the dynamics of industrialization, it is hoped that Indonesia’s future economic development can achieve a better balance between growth and sustainability.